International Organizations - Schiavone, Giuseppe. author. aut Link
V, 334 p.
Keywords: Dramatic changes in the world order since 1992 - the continuing struggle in the former Yugoslavia, the creation of the World Trade Organization, the tentative steps towards European Union - have led to major revisions of Professor Schiavone's International Organizations . New entries, including the G-7, G-24, and the International Committee of the Red Cross, have been added. On the 50th anniversary of the UN special annexes on peace-keeping agencies and major resolutions are now included. The introductory essay contains an overall view of the basic features of the law of international organizations and a survey of their historical development and outstanding problems, helping the reader to set the organizations in their proper context, be it global or sectional. The main body of the book consists of alphabetically arranged entries for over 200 organizations - from the UN to specialised agencies and regional bodies in Europe, the Americas, the Middle East, Africa, Asia and the Pacific. Each entry is broken up into sub-headings such as Purpose, Structure, Origin and Development, and Activities. Specific data concerning addresses, principal officers, main periodic publications and a short list of works of reference are provided with each entry. Ease of access to all entries is expedited by an index of acronyms and full names. Membership charts, a table of foundation dates and a classified index complete the volume.